Changes of Cytokines in Children With Tic Disorder - Tao, Yilin; Xu, Peng; Zhu, Weiyi; Chen, Zhiyue; Tao, Xiaohan; Liu, Jiajing; Xue, Ziru; Zhu, Tao; Jiang, Peifang (Frontiers in Neurology, 2022)
Tic disorder (TD) is a common childhood-onset disease associated with abnormal development of brain networks involved in the motor and sensory processing. The underlying pathophysiological mechanisms in TD are still unclear. An involvement of immune mechanisms in its pathophysiology has been proposed. This study investigates the association between the changes of cytokines and the etiology and development of TD. Different expressions of cytokines in a larger number of samples in our study may provide new insights to the field. The levels of cytokines (IL-2, IL-4, IL-6, IL-10, TNF-α, and IFN-γ) were evaluated in 1,724 patients who were clinically diagnosed with TD from 1 to 17.5 years old and 550 were from 6 months to 14.5 years old in the control group. We assessed the levels of cytokines according to the patient's medication status and the severity of the disease. Of the cytokines we investigated, the serum IL-6 concentration of children with TD was significantly higher than that of the control group, while the levels of other cytokines were lower in TD patients. In the patient group whose YTGSS score ranged from 1 to 9, the IL-4, IL-10, and IFN-γ levels increased in medication group compared to unmedication group. Our data suggested that the cytokines (IL-2, IL-4, IL-6, IL-10, TNF-α, and IFN-γ) may play an important role in the etiology and the severity in TD. Whether drug intervention in the early stage of tic disorder has a better effect on children needs further research.